(untitled) (Research, Society and Development, 2021)
The new coronavirus infection, discovered at the end of 2019 in China, spread around the world rapidly, reaching all continents, and was then declared a pandemic by the World Health Organization (WHO). In order to inhibit the transmission of the disease, several restrictive measures were adopted by public authorities, which determined a series of changes in the functioning of society. In addition to the infectious disease itself, COVID-19 has a profound impact on the mental health of the population, with social and neuropsychiatric repercussions. Thus, the present study aimed to analyze the main aspects involved pointed out in the literature, through the review of studies conducted with different populations in Brazil and worldwide, thus outlineing the main points of discussion. To fulfill this purpose, we opted for a narrative literature review based on the search for articles related to social, neuropsychiatric and mental health aspects in the context of the COVID-19 pandemic, in the databases "PubMed", "Scielo" and "Google Scholar". As a result, it was observed that the COVID-19 pandemic is involved in a series of changes in the social sphere, with significant emotional impact, and neuropsychiatric repercussions causing several symptoms associated with major mental health disorders. In this sense, it can be affirmed, therefore, that the COVID-19 pandemic should be understood as much more than just the danger of infectious disease, and that its impact on the mental health of the population should not be neglected, but studied more thoroughly and combated by the competent authorities.